2012
DOI: 10.3109/02652048.2012.726280
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization andin vivoevaluation of solid self-nanoemulsifying drug delivery system for oral administration of docetaxel

Abstract: To formulate a self-nanoemulsifying drug delivery system (SNEDDS) for the oral administration of docetaxel as an alternative to commercial docetaxel-loaded injectable products, it was prepared by spray-drying an aqueous solution containing liquid SNEDDS and colloidal silica. Its physicochemical properties and oral bioavailability were investigated compared to a clear docetaxel solution administered intravenously or orally to rats. In the docetaxel-loaded solid SNEDDS prepared with colloidal silica, the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Solubility screening of DCT has been reported with several excipients, of which Capryol 90 and Transcutol HP showed the highest solubility612. In our study, DCT also showed higher solubility in Transcutol HP and Capryol 90, thus these were selected as appropriate co-surfactants and oil, respectively for the development of D-SEDDS.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Solubility screening of DCT has been reported with several excipients, of which Capryol 90 and Transcutol HP showed the highest solubility612. In our study, DCT also showed higher solubility in Transcutol HP and Capryol 90, thus these were selected as appropriate co-surfactants and oil, respectively for the development of D-SEDDS.…”
Section: Discussionsupporting
confidence: 51%
“…Several commonly used excipients in SEDDS such as Cremophor, Tween 80, Labrasol and Transcutol HP could inhibit the function of P-gp mediated drug efflux 6 9 10 11 . Capryol 90 (Polyethylene glycol monocaprylate) and Transcutol (Diethylene glycol monoethyl ether) lead to better solubilization of DCT compared to other lipids and co-emulsifiers 6 12 . Gelucire 44/14 (PEG-32 lauric glyceride, HLB 14) and Vitamin E TPGS (Vit E TPGS) (α-Tocopherol PEG 1000 succinate) have been shown to cause highest P-gp efflux activity among all emulsifiers 13 14 15 .…”
mentioning
confidence: 99%
“…These SNEDDS produced a nanoemulsion in water and showed 12.5% absolute bioavailability as compared to a clear DTX solution given either via IV or orally. 109 Another approach used to enhance the oral bioavailability of DTX used a solid supersaturable emulsifying drug delivery system. The system showed improved oral bioavailability of DTX in rats, as revealed by an 8.77-and 1.45-fold increased area under the curve as compared to DTX and conventional SEDDS.…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…Oil (Capmul MCM), surfactant (Cremophor EL) and co-surfactant (Transcutol P) were selected for L-SMEDDS. The L-SMEDDS was prepared as reported in literature [25] . Piroxicam (10 mg) was transferred into a screw-capped glass vial containing selected oil, surfactant and co-surfactant mixture (S-Cos mix in 2:1 ratio) and stirred with vortex to obtain homogenous solution.…”
Section: Formulation Of Liquid Smedds (L-smedds)mentioning
confidence: 99%